Swift and portable detection of soybean mosaic virus SC7 through RNA extraction and loop-mediated isothermal amplification using lateral flow device - Guo, Shui-Xian; Zhang, Qing; Bai, Nan-Nan; Yue, Pei-Yao; Niu, Jing-Ping; Yin, Cong-Cong; Yue, Ai-Qin; Du, Wei-Jun; Zhao, Jin-Zhong (Frontiers in Microbiology, 2025)
The soybean mosaic disease—caused by the soybean mosaic virus (SMV)—significantly impacts soybean quality and yield. Among its various strains, SMV-SC7 is prevalent in China. Therefore, rapid and accurate diagnosis is deemed critical to mitigate the spread of SMV-SC7. In this study, a simple and rapid magnetic bead-based RNA extraction method was optimized. Furthermore, a reverse-transcription loop-mediated isothermal amplification (RT-LAMP) assay that requires no specialized equipment such as PCR Amplifier was proposed, employing a lateral flow device (LFD) for visual interpretation of SMV-SC7. The RT-LAMP-LFD approach facilitated specificity testing of SMV-SC7. Moreover, the limit of detection (LOD) of this method was as low as 10−5 ng (2.4 copies). The sensitivity of RT-LAMP-LFD was 10-fold higher than that of the colorimetric RT-LAMP method. In 194 field samples tested, the RT-LAMP-LFD detection of the SMV-SC7 had accuracy of 98.45% in comparison to RT-qPCR. In conclusion, the assay exhibited high specificity, sensitivity, and rapidity, enabling economical and portable detection of SMV-SC7 and providing technical support to identify SMV-SC7-infected soybeans.